Compostos fenólicos da casca dos frutos de Annona crassiflora com propriedades antinociceptivas, anti-inflamatórias e antioxidantes em modelos in vitro e in vivo - Justino, Allisson Benatti (2021)
The fruit peel of Annona crassiflora Mart., a species native to the Brazilian Cerrado, is a source of phenolic compounds with high antioxidant capacity. This study aimed to investigate the possible antinociceptive, anti-inflammatory and antioxidant properties of fractions rich in polyphenols from the A. crassiflora fruit peels in in vitro and in vivo models. Proinflammatory cytokines and nitric oxide (NO) production were evaluated in LPS-activated macrophages. The ethyl acetate fraction, being able to reduce the production of inflammatory mediators in macrophages, was administered orally in C57BL/6/J mice, and the animals were subjected to glutamate-induced nociception, Freund's adjuvant (CFA)-induced inflammation, and open field and rotarod tests for motor performance analysis. The n-butanol fraction, which showed the highest antioxidant capacity among the fractions, was investigated against hepatic oxidative and nitrosative stress in diabetic Wistar rats induced by streptozotocin. Serum biochemical parameters, hepatic oxidative and nitrosative status, glutathione defense system and in silico pharmacokinetic parameters of the main compounds of the fraction were evaluated. As results, the ethyl acetate fraction inhibited IL-6 and NO production in LPS-induced macrophages at concentrations of 0.1 and 0.3 µg/mL (p < 0.001) and reduced glutamate-induced nociception by 75 ± 7% at the dose of 30 mg/kg (p < 0.001), without changing the locomotor activity of the animals. In addition, the ethyl acetate fraction (30 mg/kg) was able to reverse the CFA-induced acute and late hyperalgesia (p < 0.05), in addition to reducing edema in the acute phase (p <0.05), with reductions in myeloperoxidase activity (40 ± 12%, p < 0.05) and inflammatory polymorphonuclear cell infiltration in the paw tissue (40 ± 9%, p < 0.001). The treatment of diabetic rats with the n-butanol fraction for 30 days, at the dose of 50 mg/kg, decreased the serum activities of alanine aminotransferase, aspartate aminotransferase and alkaline phosphatase (p < 0.01), in addition to reducing in the hepatic lipid peroxidation, protein carbonylation and nitration, the level of inducible nitric oxide synthase and the activities and expressions of glutathione peroxidase, superoxide dismutase and catalase (p < 0.05). There were also increases in antioxidant capacity, glutathione reductase activity and reduced glutathione level (p < 0.05). The in silico predictions of the phenolic compounds present in the fraction showed favorable absorption and distribution, without possible signs of hepatotoxicity. The results support the antinociceptive, anti-inflammatory and hepatoprotective effects of A. crassiflora fruit peel, and suggest that these effects are triggered by the suppression of pro-inflammatory cytokines, reduction of neutrophil infiltration, and improvement of hepatic oxidative/nitrosative parameters.